2018
DOI: 10.1002/acn3.601
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic white matter integrity loss in familial frontotemporal dementia in the GENFI cohort: A cross‐sectional diffusion tensor imaging study

Abstract: ObjectiveWe aimed to investigate mutation‐specific white matter (WM) integrity changes in presymptomatic and symptomatic mutation carriers of the C9orf72,MAPT, and GRN mutations by use of diffusion‐weighted imaging within the Genetic Frontotemporal dementia Initiative (GENFI) study.MethodsOne hundred and forty mutation carriers (54 C9orf72, 30 MAPT, 56 GRN), 104 presymptomatic and 36 symptomatic, and 115 noncarriers underwent 3T diffusion tensor imaging. Linear mixed effects models were used to examine the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 51 publications
(81 reference statements)
2
41
0
Order By: Relevance
“…As indicated in sMRI, left-right asymmetry was also found in most white matter tracts of GRN mutation carriers. The most consistent asymmetry was reported in the uncinate fasciculus, retrolenticular part, and anterior limb of the internal capsule, as well as external capsule (36). However, the development of asymmetry over time may have different patterns in various white matter tracts.…”
Section: Grn_dtimentioning
confidence: 84%
See 3 more Smart Citations
“…As indicated in sMRI, left-right asymmetry was also found in most white matter tracts of GRN mutation carriers. The most consistent asymmetry was reported in the uncinate fasciculus, retrolenticular part, and anterior limb of the internal capsule, as well as external capsule (36). However, the development of asymmetry over time may have different patterns in various white matter tracts.…”
Section: Grn_dtimentioning
confidence: 84%
“…White matter involvement from DTI studies in asymptomatic GRN mutation carriers showed reduced FA in the left uncinate fasciculus, left inferior occipitofrontal fasciculus, and the genu of the corpus callosum (55). Reduced FA and increased diffusivity in the internal capsule was also reported (36). Another DTI investigation did not find a difference in FA, MD, and RD, but reported increased AD in the right cingulum, superior longitudinal fasciculus, and corticospinal tract (25).…”
Section: Grn_dtimentioning
confidence: 96%
See 2 more Smart Citations
“…Our findings are consistent with the trajectories reported in a recent longitudinal study of converters with MAPT and GRN mutations, demonstrating that loss of white matter integrity and grey matter volume were present 2 years before symptom onset. 11 In addition, previous cross-sectional studies in asymptomatic MAPT mutation carriers report presence of 1 H MRS metabolite ratio abnormalities, 3 grey matter atrophy, 12 loss of white matter integrity, 13 and functional connectivity 14 with range of 5 to 30 years before the estimated age of symptom onset. It should be noted that the cross-sectional studies estimated the age of onset by the information available from the carriers of the MAPT mutation type.…”
Section: Discussionmentioning
confidence: 94%